Surgical resection of pediatric PRETEXT III and IV hepatoblastoma: A retrospective study investigating the need for preoperative chemotherapy - Wu, Xiongwei; Wang, Jianyong; Duan, Yuhe; Liu, Yusheng; Liu, Yao; Chen, Xin; Xia, Nan; Dong, Qian (Frontiers in Pediatrics, 2022)
Objective: This study analyzed the feasibility of upfront surgical resection for pediatric PRETEXT III and IV hepatoblastoma (HB). Methods: The clinical data of 37 children who underwent surgical resection for PRETEXT III and IV HB at our hospital were obtained retrospectively. Patients were divided into a neoadjuvant chemotherapy group (NCG; n = 19) and a routine surgery group (RSG; n = 18). Clinicopathologic characteristics, treatment regimens, and outcomes were compared between the groups. Results: The RSG had a lower incidence of portal vein involvement than the NCG (p < 0.002). The estimated 3-year event-free survival rates were similar (RSG: 89 ± 0.7% and NCG: 79 ± 0.9%, p = 0.3923). The RSG underwent fewer courses of chemotherapy than the NCG (5 vs. 6, p < 0.001). Furthermore, the RSG had lower incidences of febrile neutropenia, myelosuppression, and gastrointestinal reactions (all p < 0.05). The severity of surgery-related complications did not differ significantly. Conclusion: Upfront surgical resection in children with PRETEXT III and IV HB is safe and feasible and reduces the total number of courses and side effects of chemotherapy. The degree of vascular involvement is the most important consideration when evaluating resectability during diagnosis.